1999
DOI: 10.2105/ajph.89.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with refusal to treat HIV-infected patients: the results of a national survey of dentists in Canada.

Abstract: OBJECTIVES: This study investigated dentists refusal to treat patients who have HIV. METHODS: A survey was mailed to a random sample of all licensed dentists in Canada, with 3 follow-up attempts (n = 6444). Data were weighted to allow for probability of selection and nonresponse and analyzed with Pearson's chi 2 and multiple logistic regression. RESULTS: The response rate was 66%. Of the respondents, 32% had knowingly treated HIV-infected patients in the last year; 16% would refuse to treat HIV-infected patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
95
1
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 18 publications
11
95
1
7
Order By: Relevance
“…1,9 This was borne out in the current study where significant differences were found between those obtaining higher compared with lower oral knowledge scores and willingness to treat various 'at risk' patient groups. For instance, those with higher scores were significantly more likely than lower scorers to respond that they would 'have no hesitation' in treating the following patients groups: a homosexual/bisexual man (96% compared with 78%, χ 2 = 11, df = 2, P < 0.001); a hemophiliac (77% compared with 58%, χ 2 = 6, df = 2, P < 0.05); and a HIV/AIDS patient (55% compared with 35%, χ 2 = 6, df = 2, P < 0.05).…”
Section: Correlations Between Knowledge and Attitudesmentioning
confidence: 55%
See 3 more Smart Citations
“…1,9 This was borne out in the current study where significant differences were found between those obtaining higher compared with lower oral knowledge scores and willingness to treat various 'at risk' patient groups. For instance, those with higher scores were significantly more likely than lower scorers to respond that they would 'have no hesitation' in treating the following patients groups: a homosexual/bisexual man (96% compared with 78%, χ 2 = 11, df = 2, P < 0.001); a hemophiliac (77% compared with 58%, χ 2 = 6, df = 2, P < 0.05); and a HIV/AIDS patient (55% compared with 35%, χ 2 = 6, df = 2, P < 0.05).…”
Section: Correlations Between Knowledge and Attitudesmentioning
confidence: 55%
“…Previous studies have shown that a sense of ethical responsibility is important because it is one of the strongest predictors of refusal or unwillingness to treat HIV/ AIDS patients. 9 For instance, in the McCarthy et al (1999) study, it was found that respondents who did not have a sense of ethical responsibility were nine times more likely to report that they would refuse to treat HIV infected patients than respondents who believed they did have such an ethical responsibility. In this respect, it is interesting to note the significant correlations which exist in the current investigation between the statement 'As a dentist, I have an ethical responsibility to provide dental care to a HIV positive person' and the variables addressing attitudes towards various 'at risk' patients (see Table 6).…”
Section: Ethical Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Algunos estudios han mostrado que el rechazo para atender pacientes con diagnóstico de VIH se explica por la falta de compromiso ético y profesional (12,16). Los resultados de esta investigación sugieren que existe mayor oportunidad de atender pacientes VIH+ cuando los estudiantes se sienten ética o profesionalmente comprometidos.…”
Section: Discussionunclassified